PELATIHAN APLIKASI TEKNIK PENGUKUSAN PEWARNA ALAMI BERBASIS TEMPATAN PADA BAHAN SUTRA DI KELOMPOK ASOSIASI BAWI DAYAK KOTA PALANGKA RAYA - Misrita, Misrita; Yusintha Tanduh; Imam Qalyubi; Stevin Carolus Angga (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
This article describes comprehensive training centered on applying the technique of steaming natural dyes sourced from local plants to silk in ecoprint batik, which was carried out at the Bawi DayakAssociation group located in Palangka Raya City. Natural dyes, derived from native flora, play an important role in preserving cultural heritage, encouraging sustainable practices, and promoting environmentally friendly alternatives to synthetic dyes. This training program aims to empower members of the Bawi DayakAssociation with the knowledge and skills needed to proficiently apply the technique of steaming natural dyes to silk fabric in ecoprint batik. This service aims to increase partners' knowledge and skills regarding making ecoprints using the steaming technique, 1) providing information to mothers about steaming techniques to make colors and motifs, and 2) training mothers in making ecoprints using the steaming technique. The socialization stage is carried out through socializing the eco-printing steaming technique as an environmentally friendly product and introducing materials for eco-printing production. Ecoprinting training using the steaming technique includes the following stages: wetting (wetting the silk fabric), attaching sheets of natural flora leaves to the silk fabric, steaming and fixing. This will improve the skills of our partners who make natural dyeing ecoprints with the steaming technique and provide them with better income